Development Of The Morea Pool Tourism Object In Larike State West Leihitu District, Central Maluku District - Sandra Arfa Ely; J. F. Sopamena; N. F. Wenno (International Journal of Economics, Business and Innovation Research, 2024)
In the current era of globalization, progress in the tourism sector is very rapid. Tourism has been recognized as the largest industry of this century. Judging from various world development indicators, in the coming years the role of tourism will increase. Therefore, much needs to be done to develop tourism potential, especially in Indonesia. Central Maluku, as one of the districts in Maluku, is of course one of the areas most sought after by local and foreign tourists. Central Maluku Regency has a geographical location consisting of mountainous areas and coastal areas so it has a variety of ethnicities, cultures, and other tourist attractions, making it interesting to visit nationally and internationally, one of which is the Morea Pool. The research location is in Negeri Larike, West Leihitu District, Central Maluku Regency. Research time is January 2023 - February 2023. From the results and discussion, it can be concluded that the management of the Morea Pond tourist attraction is still not optimal, namely in terms of development and institutions. Increasing and developing tourism can be carried out by involving community participation in supporting the development of infrastructure and facilities and strategies for developing the Morea Pond tourist attraction, namely by increasing promotion of the Morea Pond tourist attraction and maintaining the things that are the selling points of Morea Pond.